Evaluation of conservation tillage practices for enhancing productivity of sunflower (Helianthus annuus L.) under rice fallow environment of Odisha: EVALUATION OF TILLAGE PRACTICES FOR ENHANCING PRODUCTIVITY OF SUNFLOWER - K RAMESH; D PATEL; A MAHAPATRA; S N JENA (Journal of Oilseeds Research, 2020)
Field experiment was conducted to assess the effect of conservation tillage (reduced, minimum and zero tillage) and conventional tillage with three hybrids (DRSH-1, KBSH-44, MSFH-17) and three fertility levels (50% RDF, 100% RDF and 150% RDF) on productivity of sunflower. Zero tillage recorded highest growth parameters, yield attributing characters and seed yield (1.91 t/ha), stover yield (4.36 t/ha) and oil yield (0.73 t/ha). Crop grown under zero tillage conditions was taller (165.7 cm), had more number of leaves/plant (30.3) and accumulated more dry matter (565 g/m2). Among the hybrids, KBSH-44 recorded the highest seed yield (1.81 t/ha), stover yield (4.22 t/ha) and oil yield (0.70 t/ha). Sunflower fertilized with 150% RDF recorded significantly highest seed yield (2.09 t/ha), stover yield (5.0 t/ha) and oil yield (0.81 t/ha) as well as the highest values of yield attributing characters which were promoted by the better growth attributing characters. Sunflower hybrids under zero tillage fertilized with 150% RDF (90:120:90 kg N: P2O5: K2O/ha) found most remunerative under rice fallow environment.